Are tree squirrels involved in the circulation of flaviviruses in Italy?. Issue 5 (8th April 2018) - Romeo, C.; Lecollinet, S.; Caballero, J.; Isla, J.; Luzzago, C.; Ferrari, N.; García‐Bocanegra, I.
Summary: West Nile virus (WNV), Usutu virus (USUV) and tick‐borne encephalitis virus (TBEV) are emerging zoonotic flaviviruses (family Flaviviridae ), which have circulated in Europe in the past decade. A cross‐sectional study was conducted to assess exposure to these antigenically related flaviviruses in eastern grey squirrels ( Sciurus carolinensis ) in Italy. Seventeen out of 158 (10.8%; CI95% : 5.9‐15.6) squirrels' sera tested through bELISA had antibodies against flaviviruses. Specific neutralizing antibodies to WNV, USUV and TBEV were detected by virus neutralization tests. Our results indicate that tree squirrels are exposed to Culex and tick‐borne zoonotic flaviviruses in Italy. Moreover, this study shows for the first time USUV and TBEV exposure in grey squirrels, broadening the host range reported for these viruses. Even though further studies are needed to define the real role of tree squirrels in the epidemiology of flaviviruses in Europe, this study highlights that serology could be an effective approach for future investigations aimed at broadening our knowledge about the species exposed to these zoonotic infections.